P89 Attendance Of Secondary Care Respiratory Outpatient Appointments In Illicit Drug Users With Recurrent Hospital Admissions With 'copd' At A City Centre Teaching Hospital. (10th November 2014) - Huang, R; Collins, AM; Williams, N; Garner, N; Perry, T; Burhan, H
Abstract : Introduction: Non-attendance at outpatient appointments (OPA) costs the NHS an estimated £600 m a year, with over 94, 000 missed (first) OPAs in England from 2013 to 2014. 1 We reviewed the arrangement and attendance of OPAs for illicit drug smokers, after hospital re-admission with an 'exacerbation of chronic obstructive pulmonary disease (COPD)'. Methods: All illicit drug smokers re-admitted between January 2009 and September 2011 with a presumptive diagnosis of 'exacerbation of COPD' were included. Planned respiratory OPAs were reviewed retrospectively from our COPD admission database to determine the number attended or unattended. Unattended OPAs were classified as (a) hospital cancellation (b) patient cancellation (c) patient did not attend (DNA) or (d) 'unknown'. Results: Of 89 patients, no OPA was arranged in 28 (31.5%). 334 respiratory appointments were made for 61 patients (mean = 5.5 per patient); of these, only 86 (25.7%) were attended (see Table). Conclusion: High recurrent admission rates suggests that these patients should all have specialist respiratory OPAs arranged at discharge, with the aim of preventing re-admission and improving their respiratory health. In our cohort we noted poor OPA attendance with a DNA rate of 52.0% compared with around 8.6% for first OPAs overall in England in 2012. 2 This suggests alternative approaches are needed in order to engage with these patients such as community based secondary care outreach services. We will now study the effects of an intensive community-based secondary care outreach services; involving smoking cessation, targeted pulmonary rehabilitation, specialist respiratory (consultant and nurse) involvement, vaccination, inhaler technique reviews, medication concordance checks/ prescription and health trainers. References: Department of Health (2014). Referrals and Attendances for Outpatient Appointments: Hospital Activity Statistics. London: DH Department of Health (2013). NHS inpatient elective admission events and outpatient referrals and attendances, quarter ending December 2012. Available from: http://www.england.nhs.uk/statistics/2013/02/22/nhs-inpatient-elective-admission-events-and-outpatient-referrals-and-attendances-quarter-ending-december-2012